Exploring academic development programme evaluation at a university: A systematic scholarly approach - Johannes, H.; Batyi, T.T.; Goldstone, S.P.; Olsen, A-M.; Champion, E. (South African Journal of Higher Education, 2019)
The systematic review, critique and evaluation of Academic Development (henceforth AD) programmes are increasingly becoming important for informing ongoing and future programme design. Ensuring the relevance requires a thorough understanding of the programme to be evaluated (Chalmers and Gardiner, 2015). This paper reports on the findings from a study exploring the nature of AD programmes at the University – with the aim of constructing a conceptual framework for thinking about AD programmes. This is necessary, in order to determine and evaluate the characteristics of nine programmes; and to determine whether these include the promotion of conceptual change – to thinking differently about teaching and learning in Higher Education. The process of re-contextualising teaching, learning and assessment at the University from a common-sense approach – to a more scholarly approach – includes evaluative-research methodologies, as well as critical reflection within a paradigm of system theories. The research outcomes include a conceptual framework and a blueprint for a generic AD programme design.